Transrapid, New Thought to China’s Traffic Confusion - Chu, Shao-Ying (Promet - Traffic&Transportation)
China is by far the largest unifO!m economic region of theworld. It is growing fast both in relative and in absolute terms.Principal decisions need to be taken before long to establish anadequate transport system covering distances of up to 5000 kmeasily in one day and serving numerous intermediate junctionsat short time intervals. Even long distance connections acrossthe Asian continent with India and with Europe must be takeninto consideration.